2014 Proceedings of the SICE Annual Conference (SICE) 2014
DOI: 10.1109/sice.2014.6935298
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous realization of power assist and skill assist for sinusoidal motions by using semi-active assist mechanism

Abstract: In recent years, workers decline has become a major problem in the field such as nursing care, welfare and heavy transport work in a factory with hard work. The authors have developed semi-active assist mechanisms and their control methods as wearable power assist devices for fatigue reduction. The mechanisms have elastic material as the source of assist force, and actuators for controlling the elastic force. Elastic materials such as springs retain equilibrium because their material generates the restoring fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…The proposed position control falls within admittance control (force is input, displacement is output) integrated with position feedback and velocity controller [8]. The control methods may seem to be simple (trivial), but these are highly novel as weight prediction is included in the controls and the controls seem to be extremely beneficial for the state-of-the-art PARSs [3]- [16].…”
Section: Force Control Method-2mentioning
confidence: 99%
See 2 more Smart Citations
“…The proposed position control falls within admittance control (force is input, displacement is output) integrated with position feedback and velocity controller [8]. The control methods may seem to be simple (trivial), but these are highly novel as weight prediction is included in the controls and the controls seem to be extremely beneficial for the state-of-the-art PARSs [3]- [16].…”
Section: Force Control Method-2mentioning
confidence: 99%
“…A good number of PARSs have been proposed for handling objects [3]- [16]. Kazerooni introduced the basic principles of power and information sharing for a PARS [3].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Kusaka and Tanaka studied skill assistance by using a semiactive assistance mechanism [2]. Skill assistance has been applied to various fields.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we propose skill assistance by using quantitative and real-time evaluation method with CFO [2]. Tsujita and Igarashi [3] investigated the relationship between CFO and work performance, and suggested that the relation between CFO and operation accuracy is showed negative correlation.…”
Section: Introductionmentioning
confidence: 99%